2021
DOI: 10.15386/mpr-1908
|View full text |Cite
|
Sign up to set email alerts
|

Progressive disseminated histoplasmosis in idiopathic CD4 lymphocytopenia an underdiagnosed combination - a case report

Abstract: Progressive disseminated histoplasmosis (PDH) usually presents as fever, anemia, leukopenia, hepatosplenomegaly, lymphadenopathy and pulmonary symptoms. There are few reports showed the association of Idiopathic CD4 lymphocytopenia (ICL) with histoplasmosis. We describe a 65-year-old female presented with history of fever, papulo-nodular rash and significant weight loss and diagnosed as progressive disseminated histoplasmosis. All immunocompromised conditions were ruled out.  In addition, her 2 consecutive CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Histoplasmosis, a dimorphic fungus, was a differential that was considered. Commonly found in soils and yeast forms, its portal of entry is through inhalation [ 18 ]. Patient was tested for histoplasmosis through urine studies and was found to be negative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histoplasmosis, a dimorphic fungus, was a differential that was considered. Commonly found in soils and yeast forms, its portal of entry is through inhalation [ 18 ]. Patient was tested for histoplasmosis through urine studies and was found to be negative.…”
Section: Discussionmentioning
confidence: 99%
“…Before the highly active antiretroviral therapy (HAART) medication becoming an effective medication of HIV/AIDs, Coccidioides was a significant opportunistic infection for patients with HIV living in endemic regions as their immune responses were unable to control the viral replication and immune reconstitution without the use of HAART [ 18 ]. It is suggested in data that a peripheral CD4 count ≥ 250/µL can maintain an immune response against any coccidioidal manifestations [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, depletion of CD4 T cells during primary fungal infections promotes survival, whereas depletion of CD8 T cells attenuates fungal clearance in the primary infection. Remarkably, Vβ4+ T cells which are CD8 T cell subtypes are preferentially activated during pulmonary histoplasmosis, and contribute to the generation of protective immunity by recognizing HSP60 from H. capsulatum , and the elimination of these immune cells prevents the resolution of this infection in mice 38,39 . Progressive disseminated pulmonary histoplasmosis is most commonly recognized in AIDS patients, idiopathic lymphocytopenia, and common variable immunodeficiency 39 .…”
Section: Pulmonary Histoplasmosis and Immune Responsementioning
confidence: 99%
“…Progressive disseminated pulmonary histoplasmosis is most commonly recognized in AIDS patients, idiopathic lymphocytopenia, and common variable immunodeficiency 39 . An observational study illustrated that pulmonary histoplasmosis was common in patients with lymphoma and leukemia treated with bendamustine chemotherapy 38 . Over‐activation of Th17 and reduction of regulatory T cells (Treg) are associated with the acceleration and clearance of fungal infections, including H. capsulatum 40 .…”
Section: Pulmonary Histoplasmosis and Immune Responsementioning
confidence: 99%
See 1 more Smart Citation